2003
DOI: 10.1074/jbc.m210353200
|View full text |Cite
|
Sign up to set email alerts
|

Xenorhabdus nematophila (Enterobacteriacea) Secretes a Cation-selective Calcium-independent Porin Which Causes Vacuolation of the Rough Endoplasmic Reticulum and Cell Lysis

Abstract: Xenorhabdus nematophila and Photorhabdus luminescens are two related enterobacteriaceae studied for their use in biological control and for synthesis of original virulence factors and new kinds of antibiotics. X. nematophila broth growth exhibits different cytotoxic activities on insect (Spodoptera littoralis, lepidoptera) immunocytes (hemocytes). Here we report the purification of the flhDC-dependent cytotoxin, a 10,790-Da peptide we have called ␣-Xenorhabdolysin (␣X). We show that plasma membrane of insect h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 36 publications
(32 reference statements)
2
33
0
Order By: Relevance
“…ShlA-induced vacuoles, however, do not appear to be derived from late endosomes. Alpha toxin of Xenorhabdus triggers endoplasmic reticulum vacuolation by increasing monovalent cation permeability of the membrane, resulting in cell death by colloid-osmotic lysis (Ribeiro et al, 2003). An early in vivo study showed that V. parahaemolyticus-infected mice displayed congestion, oedema and vacuolation in mucosal and submucosal tissues (Hoashi et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…ShlA-induced vacuoles, however, do not appear to be derived from late endosomes. Alpha toxin of Xenorhabdus triggers endoplasmic reticulum vacuolation by increasing monovalent cation permeability of the membrane, resulting in cell death by colloid-osmotic lysis (Ribeiro et al, 2003). An early in vivo study showed that V. parahaemolyticus-infected mice displayed congestion, oedema and vacuolation in mucosal and submucosal tissues (Hoashi et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have shown that the nematobacterial complex attenuates insect cellular reactions in the hemolymph. The inhibition of nodule formation was studied in vivo (8,16,17), and cytotoxic factors active against hemocytes have been identified in vitro (4,21,22). The mode of action of a cytolytic factor on immunocytes (cells of the insect hemolymph) was recently characterized in detail (22).…”
mentioning
confidence: 99%
“…The size variation could be due to differences in the lipid composition of the membranes in liposomes and the target cells, allowing variable numbers of subunits to assemble in the pore. Toxin proteins producing pores of different size in different cell types have been reported earlier (30).…”
Section: Fig 2 Effect Of Mrxa On Larval Hemocytes and Their Protectmentioning
confidence: 99%
“…Pore-forming toxic proteins facilitate entry of the pathogen and/or damage the host cell for their own ends. In addition to the orally toxic proteins (7), X. nematophila is reported to produce a 10-kDa cytotoxic, cation-selective channel-forming protein in the culture medium (30). To understand the mode of action of cytotoxic fimbrial subunit MrxA of X. nematophila, we have investigated the pore-forming activity of the protein.…”
mentioning
confidence: 99%